1980
DOI: 10.1042/bst0080215
|View full text |Cite
|
Sign up to set email alerts
|

ADP-ribosylation of nuclear proteins

Abstract: ADP-ribosylation can be defined as the postsynthetic modification of protein by the covalent attachment of the ADP-ribose moiety of NAD+. ADP-ribosylation of elongation-factor Tu is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…It has been suggested that the nuclear location of NAD pyrophosphorylase is related to the involvement of NAD+ in the regulation of cellular activity [6] and a correlation between NAD pyrophosphorylase activity and mitosis has been observed [7, 81; there are also numerous examples of a correlation between NAD pyrophosphorylase activity and DNA synthesis [4,. This suggestion was supported by the discovery of a chromosomal protein, poly(ADP-ribose) synthetase [13 -151, which uses NAD' as a substrate for the post-translational modification of nuclear proteins [16,17], including histones [I 8, 191. Although the precise physiological role of this enzyme remains unclear, there is evidence that poly(ADP-ribosy1)ation is involved in DNA replication, mitosis, transcription and the repair of damaged DNA [17, 20- only a small amount of exchange occurs and the reasonable conclusion was made that there is no support for an adenylylenzyme intermediate [24].…”
mentioning
confidence: 89%
“…It has been suggested that the nuclear location of NAD pyrophosphorylase is related to the involvement of NAD+ in the regulation of cellular activity [6] and a correlation between NAD pyrophosphorylase activity and mitosis has been observed [7, 81; there are also numerous examples of a correlation between NAD pyrophosphorylase activity and DNA synthesis [4,. This suggestion was supported by the discovery of a chromosomal protein, poly(ADP-ribose) synthetase [13 -151, which uses NAD' as a substrate for the post-translational modification of nuclear proteins [16,17], including histones [I 8, 191. Although the precise physiological role of this enzyme remains unclear, there is evidence that poly(ADP-ribosy1)ation is involved in DNA replication, mitosis, transcription and the repair of damaged DNA [17, 20- only a small amount of exchange occurs and the reasonable conclusion was made that there is no support for an adenylylenzyme intermediate [24].…”
mentioning
confidence: 89%
“…[1][2][3][4]. Eukaryotic cells also contain endogenous proteins that are modified by single ADP-Rib residues (cf.…”
mentioning
confidence: 99%
“…ADP-ribosyl transferase is a nuclear enzyme that transfers ADP-ribosyl residues from NAD ÷ to chromatin proteins, to form mono-, oligo-and poly(ADPribose) (reviews [1][2][3][4]). The enzyme is totally dependent on DNA [5] and is markedly stimulated by fragmentation of the DNA [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%